Etika Ilmu Pengetahuan dan Tanggung Jawab Sains Pertanian dalam Menjaga Keseimbangan Alam - Damayanti, Alfa Dirsista (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
The development of agricultural technologies and innovative practices is not solely aimed at increasing productivity, but must also take into account the ecological and social impacts of agricultural activities. In this context, scientific ethics and scientific responsibility serve as fundamental guidelines for researchers, practitioners, and policymakers. The method employed in this review is a literature review. Scientific ethics functions as a guiding framework to ensure that agricultural science continues to contribute to ecological balance, sustainable food production, and social justice. The responsibility of agricultural science toward maintaining ecological balance is also strongly reflected in various studies conducted in Indonesia, which emphasize the importance of sustainable natural resource management, one of which is the application of nanopesticides.